GIS for groundwater management in cities on volcanoes: example from the Colli Albani Region, Rome, Italy - Giordano, G.; Mazza, R.; Cecili, A.; Capelli, G.; Rita, D. De; Bigi, G.; Rodani, S. (Journal of Nepal Geological Society, 2000)
The Colli Albani volcanic complex contains the deposits of Quaternary stratovolcano. They cover over 1500 km2 around the city of Rome and have formed one of the most important aquifers for the city since the Roman age. Presently the volcano is quiescent, although it is characterised by shallow seismicity and gas emissions along the main fault systems. The area has undergone rapid urbanisation during the last 50 years and is presently characterised by intense, diffuse, and uncontrolled water withdrawal. In this paper we document a significant drop of water table, locally up to 100 m, which occurred during the last ten years. During the same period, there occurred several episodes of CO2 release in air that threatened human and animal life. We suggest a possible interplay between the dynamics of the hydrogeological system and the still active hydrothermal system, and present a Geographic Information System designed for the zonation of the area into various ‘water-yielding capacity’ classes as a function of aquifer depletion, urbanisation, and land use as well as hydrothermal activity and seismicity.